Posesión precaria y título, bajo el análisis de la casación 1784-12-Ica y el cuarto pleno casatorio civil - Acevedo Aguirre, María Inés (2016)
This research aimed to analyze the precarious possession, looking closer to a precise definition title possession, so we can conclude whether the existing family relationship between the applicant and demanding a process of eviction precarious occupation rule precarious same, or if the existing family relationship does not remove the fact precariously occupying the property, ie, has sought to determine within the scope of the definition of "title" own, whether within the assumptions made by the Fourth Plenum Casatorio Civil and matchings differences in this respect, as is the Cassation 1784-2012-Ica, can be interpreted or incorporate family status as enough to own a property title, and if on that basis the constitutional principle of protection applies to the family. Thus we have proceeded to analyze the relevant articles of the civil code, the Political Constitution of Peru, the Second and Fourth Plenum Civil casatorio and various matchings that address this issue which has concluded that the family relationship is not sufficient title own. Thus, the sole condition relationship with the plaintiff does not involve sufficient title to own, since in the eviction process what is defined is the right of possession, which is not the same as the + server to possession., however, there are other ways to protect the defendant in order not to be stripped of the property, as is the state of necesitad together with the right to dignity of the person protected by our Constitution